Mapping the landscape of solution-focused brief therapy : A bibliometric analysis - Janet Ann, Fernandez; Joyce Ann, Fernandez (Taylor & Francis Group, 2025)
This paper explores the evolution of Solution-Focused Brief Therapy (SFBT) using bibliometric analysis. The findings revealed 458 key publications from Scopus. The paper discusses the influential authors, leading journals, prominent institutions, and noteworthy countries involved in SFBT research. This analysis highlights the global reach of SFBT, particularly its adoption across diverse cultures and settings and its application in various domains such as mental health, education, social work, and organizational development. In addition to providing valuable insights into the trajectory of SFBT, this paper offers a roadmap for future studies and continued growth in the field.